What is the cognitive basis of the side‐effect effect? An experimental test of competing theories. (9th August 2018) - Proft, Marina; Dieball, Alexander; Rakoczy, Hannes
Abstract : Recent work on the side‐effect effect has shown that subjects' intentionality judgments are influenced by moral evaluations. In six experiments, we tested four different candidates for the cognitive foundation derived from prominent explanatory accounts (prescriptiveness, [un‐]expectedness, blame and a shift in default attitudes) against each other in three steps. First, Study 1 showed that the effect even extends to certain descriptive norms. Second, Studies 2–5 investigated the candidates more directly. Results reveal that intentionality judgments could best be explained by underlying shifts in default attitudes. Third, Study 6 experimentally manipulated this default attitude, leading to the predicted change in intentionality judgments.